Discovery of SERPINA3 as a candidate urinary biomarker of lupus nephritis activity. (4th October 2018) - Turnier, Jessica L; Brunner, Hermine I; Bennett, Michael; Aleed, Ashwaq; Gulati, Gaurav; Haffey, Wendy D; Thornton, Sherry; Wagner, Michael; Devarajan, Prasad; Witte, David; Greis, Kenneth D; Aronow, Bruce
Abstract: Objectives: We used an unbiased proteomics approach to identify candidate urine biomarkers (CUBMs) predictive of LN chronicity and pursued their validation in a larger cohort. Methods: In this cross-sectional pilot study, we selected urine collected at kidney biopsy from 20 children with varying levels of LN damage (discovery cohort) and performed proteomic analysis using isobaric tags for relative and absolute quantification (iTRAQ). We identified differentially excreted proteins based on degree of LN chronicity and sought to distinguish markers exhibiting different relative expression patterns using hierarchically clustered log10-normalized relative abundance data with linked and distinct functions by biological network analyses. For each CUBM, we performed specific ELISAs on urine from a validation cohort ( n = 41) and analysis of variance to detect differences between LN chronicity, with LN activity adjustment. We evaluated for CUBM expression in LN biopsies with immunohistochemistry. Results: iTRAQ detected 112 proteins in urine from the discovery cohort, 51 quantifiable in all replicates. Simple analysis of variance revealed four differentially expressed, chronicity-correlated proteins ( P -values < 0.05). Further correlation and network analyses led to selection of seven CUBMs for LN chronicity. In the validation cohort, none of the CUBMs distinguished LN chronicity degree; however, urine SERPINA3 demonstrated a moderate positive correlation with LN histological activity. Immunohistochemistry further demonstrated SERPINA3 staining in proximal tubular epithelial and endothelial cells. Conclusion: We identified SERPINA3, a known inhibitor of neutrophil cathepsin G and angiotensin II production, as a potential urine biomarker to help quantify LN activity.